Individual Sensitivity to Change in the Lingua Franca Use of English - Taipale, Irene; Laitinen, Mikko (Frontiers in Communication, 2022)
The study of ongoing change in English typically focuses on studying evidence from codified varieties of the language. Recent corpus studies show, however, that advanced non-native users of English may display heightened sensitivity to features undergoing frequency shifts similar to that experienced by native speakers (Laitinen 2016). In addition, most studies aiming to detect patterns of linguistic regularity utilize large data sets that attempt to minimize the presence of the individual. In this study, we focus on change in ELF and place non-native individuals at the center of attention. Our empirical section examines how aggregated features that are currently undergoing change in codified varieties of English vary in the repertoires of ELF users of Twitter. To carry out this task, this study utilizes geo-tagged tweets retrieved from the Nordic Tweet Stream (Laitinen et al. 2018). The data obtained from this real-time monitor corpus are freely available for research and re-use at https://cs.uef.fi/nts/. For the analysis itself, we selected the idiolects of 150 individual users who actively tweet in English from geographically varying locations in Finland. As American English predominates with several patterns of linguistic change in codified varieties of English (Leech et al. 2009; Baker 2017; Gonçalves et al. 2018), a simplified dichotomy between American and British features is utilized as a conceptual tool for inspecting variation. The idiolects are analyzed from the perspective of spelling and lexico-grammatical and morphological variation, such as V + -ing | V + infinitive (e.g. start doing | start to do) and expanded predicates (e.g. take a look | have a look) (Leech et al. 2009). The quantitative observations show that, particularly in the case of grammatical features, ELF speakers appear to have generally adhered to ongoing linguistic change.